2018
DOI: 10.20944/preprints201809.0111.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Consumer Preferences on the Coffee Market in Developing Central European Countries: On the Example of Poland

Abstract: The article addresses the issue of consumer preferences for types of coffee in Poland (ground coffee, instant coffee, coffee beans, instant coffee mixes and instant cappuccino). The main source of the study is the results of primary research conducted using a structured interview (CAPI—Computer Assisted Personal Interview) on a nationwide sample of 800 coffee consumers. The research was conducted by Grupa IQS Sp. z o.o. from Warsaw in January 2016 for the MOKATE Group based on the assumptions and gui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
0
1
0
Order By: Relevance
“…Many studies [ 44 , 45 , 46 , 47 , 48 , 49 ] focus on the coffee markets, including purchasing consumer behavior and quantified consumption, as well as sustainable development and ethical consumption in line with the principles of fair trade. Few data [ 47 , 50 , 51 , 52 , 53 , 54 , 55 ] concern consumption motives, consumer behavior, and preferences as to the method of coffee brewing or aspects related to the proper preparation of the infusion.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies [ 44 , 45 , 46 , 47 , 48 , 49 ] focus on the coffee markets, including purchasing consumer behavior and quantified consumption, as well as sustainable development and ethical consumption in line with the principles of fair trade. Few data [ 47 , 50 , 51 , 52 , 53 , 54 , 55 ] concern consumption motives, consumer behavior, and preferences as to the method of coffee brewing or aspects related to the proper preparation of the infusion.…”
Section: Introductionmentioning
confidence: 99%
“…In Poland, approximately 82,000 tons of coffee were sold in 2017, prompting a study involving 800 participants from different regions of the country. This four-year research revealed that 85% of the participants preferred instant coffee, and 36% of them preferred to drink ground coffee once or twice a day [51]. Table 7 shows that the research participants from MD and FT prefer ground coffee at a percentage of 46-48%, but those from EECS prefer ground coffee in 28.57%.…”
Section: Discussionmentioning
confidence: 91%